Novel foods and contemporary food challenges – selected legal aspects - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2018)
The subject of the discussion is the regulation of novel foods, in particular EU Regulation No. 2015/2283, while the aim of the article is to answer the question whether novel foods can help to meet modern food challenges, and in particular to ensure food safety and food security. The solutions adopted in the Regulation enable alternative food to be placed on the EU market, ensuring at the same time a high level of protection of consumers’ health and life. Novel foods are therefore an opportunity to make the right to food a reality, but only if it does not pose a risk to human health and life. Hence, the regulation of the placing of novel foods on the market focuses in particular on ensuring their safety.